KAJIAN AKIBAT HUKUM ISLAM TERHADAP TRANSAKSI PENUKARAN UANG DI PINGGIRAN JALAN SAMARINDA - Nugraha, Yudi Dasa (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
AbstractIn transactions, sometimes there are parties who do not know the law of the transaction they are carrying out, as an example of the practice of exchanging money during Eid, where small sums of money at that time were very difficult to find, so there were some people who considered this as a great business opportunity, it's no wonder that many are found when approaching Lebaran traders who offer small pieces of money on the streets. Based on the background mentioned above, the author wants to choose the title "Study of the Effects of Islamic Law on Money Exchange Transactions in the Suburbs of Samarinda". In the research the author uses the empirical juridical method. Based on the results of the research and discussion that has been described, the following conclusions can be taken. Imam Wahbah Az-Zuhaili emphasized that money is the current medium of exchange with gold and silver because it has the same illat, so the law is the same. Suggestions to the government to immediately hold and multiply the relevant institutions that receive new money exchange services, so that people are not reluctant to exchange them in that particular place.